Factor analyses of transformed geochemical compositional data of meme river stream sediment, Lokoja, north central Nigeria - C.S, Ngozi-Chika; A. E., Olorunyomi; H. N., Echetema; O.I, Ibrahim (International Journal of Advanced Geosciences, 2021)
Geochemical mapping using stream sediments from MRDB, north-central, Nigeria was undertaken towards obtaining multivariate association patterns reflecting the presence of ore mineralization in Lokoja region. The area is underlain by Precambrian crystalline rocks within the Benin-Nigeria Shield and clastic sedimentary rocks of Bida Basin (one of Nigeria inland sedimentary basins). The basement crystalline rocks have been known as a source of ore minerals in Nigeria. The major lithological units are cut by the Meme river watershed which have deposited in their tributaries, large quantities of alluvial and eluvial deposits formed during an extensive period of weathering and surficial processes. The PC analysis was performed on clr-transformed of Meme sediment geochemical compositional data of selected ore forming elements in the hope of obtaining geochemical information that could elucidate on the inferred ore mineralization of the region. The eight PCs explain about 93% of the total variance. The positive and negative loadings of PCs indicated the presences of oxides, sulphides, REEs and gems mineralisation in the region. Further interrogation of Spearman correlation of ilr transformed data with respect to the PC loadings indicated  well developed relationship between Sr and V (0.55), Mn and Pb (0.89), Mn and Ta (0.77), Mn and Nb (0.78), Nb vs Ta (0.98), Rb and Cr (0.59), In and As (0.64), Pb and Ga (0.78), Sb and Au (0.52), Ba and Cr (0.50). The elemental association suggests that they are either indicator of their own mineralization or are suitable pathfinders to pertinent minerals in Lokoja region. The negative correlation between Fe with other ore elements indicated that the Fe is from both proximal and dextral sources probably due to many Fe formations and mineralisation (goethite, haematite± siderite – bearing sedimentary ironstone formations in the region). The high Spearman correlation coefficients between Mn, Nb and Ta inferred that these ore elements are from the proximal sources because they are reliable pathfinders to pertinent oxides mineralisation in the region. Inferred proximal mineralisation in the region include beryl, topaz, columbite, quartzofeldspathic and quartz veins with anomalous concentration of Au as well as industrial minerals which are artisanally mined in places for industrial purposes.